2002
DOI: 10.4049/jimmunol.169.11.6231
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Adenosine 5′-Monophosphate and Calcium Induce CD152 (CTLA-4) Up-Regulation in Resting CD4+ T Lymphocytes

Abstract: The CTLA-4 (CD152) molecule is up-regulated upon T cell activation and proliferation, and plays a critical role in the inhibition of immune responses. We show in this study that cAMP induces up-regulation of CD152 in human CD4+ T lymphocytes. This effect occurs in the absence of the up-regulation of CD69 and CD25 activation markers and T cell proliferation. In addition, we found that the Ca2+ ionophore ionomycin also up-regulates CD152, and that the combination of a cAMP analog or cAMP inducers with ionomycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…Additional support for this mechanism is provided by tight link between cAMP-mediated induction of CTLA-4 and ICER in CD4 + T cells [6,11,13]. This is consistent with our data indicating that CTLA-4 blockade can disrupt accumulation of ICER/CREM, thus releasing contact-dependent T R -mediated suppression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additional support for this mechanism is provided by tight link between cAMP-mediated induction of CTLA-4 and ICER in CD4 + T cells [6,11,13]. This is consistent with our data indicating that CTLA-4 blockade can disrupt accumulation of ICER/CREM, thus releasing contact-dependent T R -mediated suppression.…”
Section: Discussionsupporting
confidence: 91%
“…Remarkably, GILZ is coexpressed in T cells with GITR [50]. This relationship appears reminiscent of cAMP-mediated induction of ICER and CTLA-4 [6,13]. Remarkably, in T R assays with B7-deficient CD25 -responders residual suppression is still detectable (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…CTLA4 gene expression was determined by RT-PCR, as previously described (20). Primers used were designed to amplify the entire coding sequence of CTLA4 (5Ј-ATGGCTTGCCTTGGATTTCAGCGGCACA AGG-3Ј and 5Ј-TCAATTGATGGGAATAAAATAAGGCTGAAATTGC-3Ј).…”
Section: Determination Of Gene Expressionmentioning
confidence: 99%
“…Recently, it has been reported that PGE 2 has this property (54). This agent up-regulates cAMP, and this element also can up-regulate CTLA-4 (55). Another group has reported that immature APCs whose maturation was blocked by a proteosome inhibitor also induce CD4 ϩ cells to express FoxP3 and develop suppressive effects (56).…”
Section: Cd25mentioning
confidence: 99%